Solar radiation in urban projects: financial analysis of a photovoltaic system for a habitation house in the metropolitan area of monterrey, nuevo leon, mexico. - Leal Iga, Javier; Leal Iga, Carlos (Revista de la Construcción. Journal of Construction, 2015)
Photovoltaic systems have been presented as an alternative to the substitution of fossil fuel energy consumption in urban development projects around the world. Their implementation is however dependent on factors with high variability, such as the amount of solar radiation that reaches the ground, climate in the area, consumption patterns, among other things. All these are a direct function of the project’s geographic location. However in the majority of cases, it is economic concerns that finally determine the feasibility of implementation. Therefore, this investigative paper carries out a financial analysis of the implementation of a photovoltaic system for two homes, one with a low degree of energy consumption, and one with a high degree of energy consumption, in the metropolitan area of Monterrey, Nuevo León, Mexico, taking into account all factors involved. Amortization tables are made with the results, where it is established the number of years required to recover the investment, with these is possible to financially evaluate the use of photovoltaic paneling that harness the solar resource in Urban Developments in the study area. Our results show that the compressive and flexural strengths of the recycled mortars decrease proportionally to the amount of natural sand replacement used. A similar behavior is observed for the shrinkage due to drying in mortars with low ceramic substitutions (10%, 20% and 30%). Based on these findings, we believe that the use of mortars made with recycled sand (with substitution contents lower than 30%) could be feasible in applications where the mechanical requirements are low.